Infiltrasi dan Aliran Permukaan sebagai Respon Perlakuan Konservasi Vegetatif pada Pertanaman Kakao - ., Nurmi; Haridjaja, O.; Arsyad, S.; Yahya, S. (Jurnal Agroteknotropika, 2012)
Cacao plant is one of the major commodities of plantation in South East Sulawesi, especially in Konawe regency. Practices of land management implemented by the local farmers to produce this cacao, in many cases are not according to soil and water conservation principles. The research was aimed to investigating the rate of infiltration and runoff on the loca farmers cacao cropping land at different slope as related to canopy cover. The research was conducted in Amosilu village, Besulutu district, Konawe regency, the province of South East Sulawesi, from December 2006 to September 2007. The experimental method with field study was applied in split plot design consisting three factors, namely (i) slope consisting two levels (10-15% and 40-45%) and (ii) age of the cacao plant consisting two levels (5 to 7 month and 25 to 27 month) were used as main plots (P1 = 5 to 7 month and 10-15%; P2 = 25 to 27 month and 10-15%; P3 = 5 to 7 month and 40-45%; and P4 = 25 to 27 month and 40-45%), while (iii) vegetative conservation treatment was used as sub plots consisting three levels, i.e T1 = cacao with disc clearing, T2 = dry field rice and soybean rotation within cacao plant, T3 = T2 + Arachis pintoi as strip plant. There was not interaction between both cacao plant and slope treatment with vegetative conservation treatment to water infiltration and runoff. The result showed that vegetative conservation treatment (T1) that is cacao with disc clearing was best alternative because they were produced the higher rate of total volume of infiltration(18.69 mm) and the lower rate of runoff (2715.44 m3 ha-1 year-1). Analysis of data with ANOVA (analysis of variance) and Duncan Multiple Range Test (P < 0,05) were done by using SAS program.